Peran Psikodrama dalam Mengembangkan Empati dan Komunikasi dalam Konseling Kelompok - M. Fazli; Yeni Karneli; Netrawati Netrawati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Psychodrama is one of the approaches in group counseling that combines dramatic techniques to explore individual psychological problems. This article aims to examine the role of psychodrama in developing empathy and communication between group members. The method used is a literature study by analyzing various scientific sources related to the practice and effectiveness of psychodrama in the context of group counseling. The results of the study indicate that psychodrama is able to increase empathy through role reversal and exploration of emotions in an interpersonal context. In addition, this technique also strengthens communication skills, such as active listening, expressing feelings assertively, and building healthy relationships between group members. These findings support the importance of integrating psychodrama in group counseling services as a means of developing social and emotional skills, especially among adolescents and young adults.